Homology Modeling and Molecular Dynamics Simulations of the Active State of the Nociceptin Receptor (NOP) Reveals New Insights Into Agonist Binding And Activation - Daga, Pankaj R. (2012)
The opioid receptor-like receptor ORL1, also known as the nociceptin receptor (NOP), is a Class A GPCR in the opioid receptor family. Although NOP shares a significant homology with the other opioid receptors, it does not bind known opioid ligands and has been shown to have a distinct mechanism of activation compared to the closely-related opioid receptors mu, delta and kappa. Previously reported homology models of the NOP receptor, based on the inactive-state GPCR crystal structures, give limited information on the activation and selectivity features of this fourth member of the opioid receptor family. We report here the first active-state homology model of the NOP receptor based on the opsin GPCR crystal structure. An inactive-state homology model of NOP was also built using a multiple template approach. Molecular dynamics simulation of the active-state NOP model and comparison to the inactive-state model suggests that NOP activation involves movements of TM3 and TM6 and several activation microswitches consistent with GPCR activation. Docking of the selective non-peptidic NOP agonist ligand Ro 64-6198 into the active-state model reveals active-site residues in NOP that play a role in the high selectivity of this ligand for NOP over the other opioid receptors. Docking the shortest active fragment of endogenous agonist nociceptin/orphaninFQ (residues 1–13) shows that the NOP EL2 loop interacts with the positively charged residues (8–13) of N/OFQ. Both agonists show extensive polar interactions with residues at the extracellular end of the transmembrane domain and EL2 loop, suggesting agonist-induced re-organization of polar networks, during receptor activation.